2012
DOI: 10.1134/s0362119712010082
|View full text |Cite
|
Sign up to set email alerts
|

Association of muscle-specific creatine kinase (CKMM) gene polymorphism with physical performance of athletes

Abstract: The energy supply for muscle activity is one of the factors that determine human physical performance. Therefore, identification of genetic markers determin ing the efficiency of the adenosine triphosphate (ATP) resynthesis pathway is one of the priority trends in phys iology and genetics. For reaching the elite status, an athlete must have certain physical qualities greatly depending on genetic characteristics.During physical exercise, adenosine diphosphate (ADP) accumulates in contracting muscles triggering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 26 publications
2
39
1
3
Order By: Relevance
“…The CKMM AA genotype was associated with high values of VO 2 max and this result showed that Iranian athletes and non-athletes had more endurance potential (4). As the G allele is the rare allele for the CKM-NcoI polymorphism, researchers have speculated that this allele is associated with a protective mechanism against muscle breakdown (15).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The CKMM AA genotype was associated with high values of VO 2 max and this result showed that Iranian athletes and non-athletes had more endurance potential (4). As the G allele is the rare allele for the CKM-NcoI polymorphism, researchers have speculated that this allele is associated with a protective mechanism against muscle breakdown (15).…”
Section: Discussionmentioning
confidence: 92%
“…Especially, efficiency of the adenosine triphosphate (ATP) synthesizing resources seems to be important. In muscle tissues, the muscle isoform of creatine kinase (CKM) is a key enzyme of energy supply (2)(3)(4)(5). CK-MM is located at the surface of myosin filaments near actomyosin ATPase and is involved in the provision of the energy for the working myosin heads, supplying them with newly synthesized ATP in the course of muscle contraction (6).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning allele frequency (Figure 2), from the studies analysed the following results were observed when combat sports athletes and controls were compared: (1) ACTN3 -no difference for the three studies that investigated it (Kikuchi et al, 2012;Kikuchi et al, 2013;Rodríguez-Romo et al, 2013); (2) ACE -two studies reported difference between the athletes and the control groups (Cieszczyk et al, 2010;Kikuchi et al, 2012); (3) PPARα -one observed higher frequency (Cieszczyk et al, 2011), but the other did not (Ahmetov et al, 2006); (4) CKM -one found a higher frequency (Fedotovskaya et al, 2013).…”
Section: Ckmmentioning
confidence: 96%
“…A/G-alleles polymorphism frequencies A higher frequency of the CKM G-allele was found in the combined cohort of Polish and Russian athletes compared with controls Fedotovskaya et al (2013) * Competitive level as described in the original articles; PPARα = peroxisome proliferator-activated receptor α gene; ACE = angiotensin-converting enzyme gene; ACTN3 = alpha-actinin skeletal muscle isoform 3 gene; CKM = muscle-specific creatine kinase gene; Hardy-Weinberg equilibrium was met in all studies for all groups investigated; judo and wrestling = grappling combat sport; boxing = striking combat sport. genes in combat sport athletes and controls.…”
Section: Ckmmentioning
confidence: 99%
See 1 more Smart Citation